Survey of Kansas cow-calf producers - W. Thompson; Jack G. Riley (Kansas Agricultural Experiment Station Research Reports, 1979)
The average producer we surveyed was 46 years old with 1 year of college. He had 125 cows and 5 bulls, usually Hereford or Angus, breeding naturally on pasture for 4 1/2 months. Most replacement heifers calved at the same time as cows. Few semen tested and only 50% pregnancy tested. Eleven percent of the cows were culled annually and 75% of the producers raised their own replacements. The average cow-calf pairs used 10 acres of pasture, 2 acres of crop residues and 1 acre of hay. Vaccinations for Blackleg (79%) and Leptospirosis (61%) were popular but less than 30% routinely vaccinated for Vibriosis or IBR. Only twenty-five percent implanted their calves, 35% used some form of preconditioning, and 40% used a wormer. Calves averaged 12 months old and 675 pounds when sold. The local auction market was the most popular (52%). In 1976-1977, when the survey was made, most producers (58%) planned to maintain their present herd size and 73% considered 50-60/cwt. (47 average) a realistic price for feeder calves at weaning.
Keywords: Cattlemen& #x27; s Day; 1979; Report of progress (Kansas State University. Agricultural Experiment Station); 350; Beef; Cow-calf producers; Vaccinations